2022
DOI: 10.22190/teme210217014h
|View full text |Cite
|
Sign up to set email alerts
|

Tourism-Led Economic Growth Hypothesis - An Empirical Investigation for Serbia

Abstract: As it is commonly believed that tourism contributes positively to economic growth, many developing countries rely on tourism in their efforts to enhance their economic conditions. Serbia has also given priority to the development of tourism industry as a part of its economic growth strategy. In this paper we analyze the long-term effects of tourism on the economic growth of Serbia. More specifically, the tourism-led economic growth (TLEG) hypothesis is tested, which implies that tourism is a trigger of Serbian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…First, tourism leads to the economic growth (TLEG) hypothesis, considering that tourism affects economic growth. Some studies validating this hypothesis are: Fahimi et al (2018) for Barbados, Cuba, Cyprus, the Dominican Republic, Fiji, Haiti, Iceland, Malta, Mauritius, and Trinidad and Tobago; Zhu & He (2021) for 29 provinces of China; Pegkas (2020) for Greece; Wijijayanti (2021) for eight countries in Southeast Asia; and Hristov-Stančić et al (2022) for Serbia.…”
Section: Literature Reviewmentioning
confidence: 96%
“…First, tourism leads to the economic growth (TLEG) hypothesis, considering that tourism affects economic growth. Some studies validating this hypothesis are: Fahimi et al (2018) for Barbados, Cuba, Cyprus, the Dominican Republic, Fiji, Haiti, Iceland, Malta, Mauritius, and Trinidad and Tobago; Zhu & He (2021) for 29 provinces of China; Pegkas (2020) for Greece; Wijijayanti (2021) for eight countries in Southeast Asia; and Hristov-Stančić et al (2022) for Serbia.…”
Section: Literature Reviewmentioning
confidence: 96%
“…(2022) indicated that tourism's contribution to economic development has been scientifically verified, and this relation can be confirmed by the Tourism-Led-Growth Hypothesis (TLGH). Consequently, many theoretical and empirical researchers have analyzed the relationship between tourism and economic growth (Antonakakis et al, 2019;Arslanturk et al, 2011;Bouzahzah & El Menyari, 2013;Brida et al, 2014Brida et al, , 2020Demiröz & Ongan, 2005;Gričar et al, 2021;Gunduz & Hatemi-J, 2005; Hristov Macroeconomic Stability and Fiscal Sustainability in the Republic of Serbia Stančić et al, 2022;Kadir & Karim, 2012;Khan et al, 2020;Kim et al, 2006;Lean & Tang, 2010;Lee & Chang, 2008;Lee, 2021;Mirović et al, 2021;Perles-Ribes et al, 2017;Pratt, 2015;Shahzad et al, 2017;Sokhanvar et al, 2018;Songling et al, 2019;Tafel & Szolnoki, 2020;Wu & Wu, 2018;Wu et al, 2022). If the mentioned studies are briefly analyzed, Demiröz and Ongan (2005) investigated the impact of international tourism receipts on the long-run economic growth of Turkey from 1980 to 2004.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The effects of the tourism sector on economic growth have been referred to in the literature as the tourism-led growth hypothesis. Research on the tourism-led growth hypothesis is still up to date (Adedoyin et al , 2022; Balsalobre-Lorente et al , 2021; Brida et al , 2016; Hristov Stančić et al , 2022; Onifade et al, 2022 ; Song and Wu, 2022; Tecel et al , 2020). However, how much employment is created by the economic growth effect created by the tourism sector is also an important research question.…”
Section: Introductionmentioning
confidence: 99%